MY SAY: Need to balance KPI - Abd Razak, Dzulkifli (2009)
For some time now, key performance indicators or KPIs have been Malaysia's new buzzword. Google it and you will get more than 31 million hits. No doubt, KPIs are being widely used in various ways to help organisations measure progress towards their goals. Though aimed more at achieving corporate or industrial objectives, they have now found their way into the public sector and academia as well. So, it is not unusual to hear academics pursuing their KPIs, like their counterparts in industry, with fervour. After all, education today is an industry and the rule of thumb is "what gets measured, gets done!" To some then, KPIs as a measure of performance are sacrosanct, as if our very life depended on them.